2022
DOI: 10.3390/informatics9010004
|View full text |Cite
|
Sign up to set email alerts
|

Automated Intracranial Hematoma Classification in Traumatic Brain Injury (TBI) Patients Using Meta-Heuristic Optimization Techniques

Abstract: Traumatic Brain Injury (TBI) is a devastating and life-threatening medical condition that can result in long-term physical and mental disabilities and even death. Early and accurate detection of Intracranial Hemorrhage (ICH) in TBI is crucial for analysis and treatment, as the condition can deteriorate significantly with time. Hence, a rapid, reliable, and cost-effective computer-aided approach that can initially capture the hematoma features is highly relevant for real-time clinical diagnostics. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Hence the CBAM module is also included along with the ECA module for strengthening the feature aggregation capability, which resulted in an improved mAP of 94.3%, thereby enhancing the performance of the YOLOV5s with SPPF network to 0.3%. Experiments (8)(9)(10)(11) were carried out to further improve the model with the introduction of the microscale head [47] and the Double ECA attention module [63]. However, it can be concluded that the YOLOV5s model with the combination of SPPF, ECA, and CBAM can perform optimized hematoma detection as compared to experiments ( 9) and ( 11) with an increase in mAP of 0.2% and 0.3% respectively.…”
Section: B Ablation Studymentioning
confidence: 95%
“…Hence the CBAM module is also included along with the ECA module for strengthening the feature aggregation capability, which resulted in an improved mAP of 94.3%, thereby enhancing the performance of the YOLOV5s with SPPF network to 0.3%. Experiments (8)(9)(10)(11) were carried out to further improve the model with the introduction of the microscale head [47] and the Double ECA attention module [63]. However, it can be concluded that the YOLOV5s model with the combination of SPPF, ECA, and CBAM can perform optimized hematoma detection as compared to experiments ( 9) and ( 11) with an increase in mAP of 0.2% and 0.3% respectively.…”
Section: B Ablation Studymentioning
confidence: 95%